2016
DOI: 10.1039/c6cp06497c
|View full text |Cite
|
Sign up to set email alerts
|

Study of the interplay between N-graphene defects and small Pd clusters for enhanced hydrogen storage via a spill-over mechanism

Abstract: The hydrogen spill-over mechanism was studied by applying Density Functional Theory. We used small palladium clusters to act as the catalyst supported on the substrate (comprised of pyridinic and pyrrolic nitrogen doped graphene), in order to study hydrogen dissociation, migration and diffusion. Charge transfer and strong binding between the catalyst and the substrate lead to dissociated states of H and prevent clusters from detaching and coalescing. In dissociated cases of H on Pd clusters, energy barriers be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…On the other hand, in the field of catalytic hydrogenation reactions, one important step is the generation of activated hydrogen. This is traditionally achieved through the catalytic dissociation of molecular hydrogen using different type of catalysts . It has been found that especially efficient has been the use of small catalytic particles, such as nanoparticles, small metallic clusters, and even individual atoms, supported on different type of surfaces .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in the field of catalytic hydrogenation reactions, one important step is the generation of activated hydrogen. This is traditionally achieved through the catalytic dissociation of molecular hydrogen using different type of catalysts . It has been found that especially efficient has been the use of small catalytic particles, such as nanoparticles, small metallic clusters, and even individual atoms, supported on different type of surfaces .…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that especially efficient has been the use of small catalytic particles, such as nanoparticles, small metallic clusters, and even individual atoms, supported on different type of surfaces . In the case of metallic clusters supported on surfaces, one relevant sequence of catalytic processes starts with the hydrogen dissociation, followed by the diffusion of hydrogen atoms through the metallic clusters, and finally, the induced spillover of the hydrogen atom over the surface, wherein the hydrogen–surface interaction is weak enough to allow easy access of reactive hydrogen . In this regard, gold has been used both, as noble metal cluster catalyst, or as support surface .…”
Section: Introductionmentioning
confidence: 99%
“…Keywords Size-dependent · Nanoparticle · Melting · Enthalpy 1 Introduction Palladium nanoparticles have received growing interest due to their novel properties such as size (Chen et al, 2016) and shape (facet) (Wang et al, 2017) dependent catalytic activity, controlled oligomerization (Zhivonitko et al, 2016) and enhanced hydrogen storage (Rangel et al, 2016). However, due to the higher surface to volume ratio (Schmidt et al, 1998;Safaei et al, 2008), the nanoparticles are known as the most unstable structures among different nanosolids.…”
mentioning
confidence: 99%
“… 18 Pd can store H 2 via PdH formation and supply H atoms to nearby medium by so-called “spill-over” mechanism. 19 Moreover, the reactive termination groups and unique layered structure of ML-Ti 3 C 2 T x may let this material considered for hydrogen storage. 20 …”
Section: Introductionmentioning
confidence: 99%